The Audit Committee as A Moderating Variable: Factors Influencing Audit Quality in Financial Sector on the IDX : THE INFLUENCE OF AUDIT TENURE, AUDIT ROTATION, AND AUDIT FEE ON AUDIT QUALITY WITH THE AUDIT COMMITTEE AS A MODERATING VARIABLE (STUDY OF FINANCIAL SECTOR COMPANIES LISTED ON THE IDX) - Andardini, Siti Eka Resti; Erlina, Erlina; Adnans, Abdhy Aulia (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2024)
This study aims to determine the effect of audit quality, namely audit tenure, audit rotation, and audit fees on audit quality in financial sector companies listed on the Indonesia Stock Exchange. In addition, this study also aims to determine whether the audit committee can be used as a moderating variable in the model. The type of data used in this research is secondary data. The technique of determining the sample is using purposive sampling. The samples obtained in this study were 17 manufacturing companies listed on the IDX from 2017 to 2021. The data analysis technique used was panel data regression analysis and interaction test (moderating) which was carried out with the help of EVIEWS version 10 software. The results in this study indicate that partial tenure audits have a positive effect on audit quality and are not significant. Audit rotation has a negative effect on audit quality and not significant. Audit fees have a negative effect on audit quality and not significant. The audit committee is unable to moderate audit tenure, audit rotation, audit fees on audit quality. The audit committee is unable to moderate audit tenure, audit rotation, audit fees on audit quality.